RETRACTED: Structural equation modeling to estimate treatment adherence based on the light triad of personality and sense of coherence in patients with type-2 diabetes: examining the mediating role of psychological well-being - Mousavi, Seyedeh Maryam; Bagheri, Seyedeh Masoumeh; Jalali Heris, Nasrin; Matbouraftar, Parisa; Azarian, Mozhdeh; Kordbagheri, Mohammadreza (Frontiers in Psychology, 2023)
Background The current study investigated the relationship between the light triad of personality and self-coherence with treatment adherence in patients with Type 2 Diabetes Mellitus (T2DM) using Structural Equation Modeling (SEM). Psychological well-being was considered a mediator variable in this SEM assessment. Method A cross-sectional study by convenience sampling was conducted, and 368 patients with T2DM were recruited from 10 private practice and general hospitals from May to November 2021 in Gilan province, Iran. The Reef’s Psychological Well-being Questionnaire, the Light Triad Rating Scale, and Antonovsky’s Sense of Coherence Scale were used for data collection. Structural equation modeling was used to examine the model fitness and identify direct/indirect relationships among variables. Data were analyzed by the SPSS (Version 26) and AMOS software (Version 24). Results The average score of light triads, sense of coherence, psychological well-being, and treatment adherence were 70.36 ± 25.55, 108.25 ± 37.68, 57.03 ± 23.84, and 106.81 ± 39.61, respectively. Model fit statistics suggest that the measurement model fits the data well: χ2 (146, N = 368) = 314.011 (p < 0.001). The SEM results showed that the light triad of personality (β = 0.12) and self-coherence (β = 0.14) were positively associated with treatment adherence. Anxiety, the light triad of personality (β = 0.12), and self-coherence (β = 0.14) affect treatment adherence indirectly through psychological well-being. Conclusion The analysis of the SEM revealed that the suggested model had a suitable goodness of fit. So, using self-coherence and psychological well-being structures in designing interventional programs is recommended to optimize treatment adherence in patients with T2DM.